Modern wheat varieties demonstrated higher grain yield and health-promoting ferulic acid than old varieties in Pakistan - Humaira Qayyum; Wenfei Tian; Xue Gong; Lie Zhi; Raza, Ali; Xianchun Xia; Jinying Gou; He Zhonghu; Awais Rasheed (American Chemical Society, 2024)
Currently, there are knowledge gaps regarding how health-promoting phenolics have changed with the breeding progress in wheat and their association with agronomic traits. A collection of historical spring wheat cultivars released in Pakistan from 1911 to 2021 were investigated for the phenolic acid composition and their relation to yield traits in three environments. The results revealed that ferulic acid content (FAC) ranged from 227 to 1423 μg g–1 in different years. A significant negative correlation was observed between thousand grain weight (TGW) and FAC in all environments. However, it was possible to identify some cultivars with both high TGW and FAC. It was identified that modern wheat cultivars released after 2000 had successively 3.3–13.6% higher FAC compared with old cultivars released before the Green Revolution (1965). Furthermore, there was a consistent positive correlation between FAC in all environments and varietal release year, supporting our claim that modern cultivars have high FAC compared to old cultivars. Among modern wheat cultivars, Zam-04, Chakwal-50, and Nawab-21 had consistently higher FAC and grain yield. The association of higher FAC with the breeding progress not only identified elite cultivars with FAC but also suggested the potential of developing cultivars with functional foods and health benefits. In this context, the results are very interesting for wheat breeders and food industry professionals in identifying wheat with a high FAC.